Polyculture of Freshwater Angelfish Pterophyllum scalare and Pacific white shrimp Litopenaeus vannamei in low-salinity water - Silva Ribeiro, Felipe de Azevedo; Diogenes, Alexandre Firmino [UNESP]; Silva Cacho, Julio Cesar; Carvalho, Thiago Lima de; Kochenborger Fernandes, Joao Batista [UNESP] (Wiley-Blackwell, 2014)
In this study, we evaluated the production potential of the polyculture of Freshwater Angelfish (Pterophyllum scalare, Cichlidae) and Pacific white shrimp (Litopenaeus vannamei). Two experimental trials were set up. The first trial entailed the use of a randomized design to investigate three treatments options: angelfish monoculture, shrimp monoculture, and fish and shrimp polyculture in 12 experimental 15m(2) ponds. In the second trial, we investigated two treatments (polyculture of caged fish and uncaged fish) in 10 experimental units. In trial 1, polyculture negatively affected fish growth and survival. However, fish did not affect shrimp growth and the greatest profit was achieved in polyculture. In trial 2, caging fish improve the growth of both fish and shrimp. An economic analysis showed the greatest profit and benefit cost ratio for caged fish compared with uncaged fish. We conclude that growing P. scalare and L. vannamei together is a better strategy than shrimp monoculture in low-salinity water. The use of caged fish in such a polyculture operation would enhance productivity and profitability.
Keywords: aquarium fish; cage; ornamental fish; economic feasibility